THE THEORETICAL BASIS FOR THE CLASSIFICATION OF CRIMINAL DRAMATIZATION, METHODS FOR THEIR IDENTIFICATION AND INVESTIGATION - Abdusaidovich, Khakberdiev Abdumurad (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT– In the conditions of modernization and reforming of the country, the law-enforcement and judicial-legal reforms are primarily aimed at comprehensive protection of human rights, freedoms and legitimate interests. This is to give the state the role of a chief reformer, to ensure the rule of law, to implement strong social policies, and gradually and gradually. There are also problems with the involvement of preliminary investigations and inquiries. This article analyzes the concept and importance of the investigation, the elements of criminal instances and instances, the investigative activity, the theory of evidence, as well as the methods of detecting and investigating instances in crime investigations. At the end of the analysis, recommendations were made on the facts that should be taken into account in the case-study practice. This article deals with these issues.